1999
DOI: 10.3354/meps187101
|View full text |Cite
|
Sign up to set email alerts
|

Colonies of Phaeocystis globosa are protected by a thin but tough skin

Abstract: ABSTRACT-Colonies of the prymnesiophyte marine microalga Phaeocystis globosa were tested for mechanical properties, permeability and biochemical composition using the rnicropipette aspiration technique. We found that the Phaeocystis colony is enclosed by a thin, yet very strong, semi-permeable skin (pore size between 1 and 4.4 nm diameter) with plastic and to a limited extent also elastic properties. Qualitative staining of single colonies with selective fluorescent dyes indicated absence of lipophilic compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(94 citation statements)
references
References 24 publications
3
86
1
3
Order By: Relevance
“…This question was raised already by Jacobsen et al in 1996 upon isolation of PpV, and it was speculated at the time that the gelatinous material the colonial cells are surrounded by serves as a protection against viral infection (Jacobsen et al 1996;. The presence of an outer thin, yet mechanically stable "skin", likely with pores <4.4 nm, has also been suggested as a defense against viral attack of the cells within the colony (Hamm et al 1999). To test these hypotheses is nevertheless not easy as colonies will always shed at least some single cells, which become readily infected.…”
Section: Resistance To Viral Infectionmentioning
confidence: 99%
“…This question was raised already by Jacobsen et al in 1996 upon isolation of PpV, and it was speculated at the time that the gelatinous material the colonial cells are surrounded by serves as a protection against viral infection (Jacobsen et al 1996;. The presence of an outer thin, yet mechanically stable "skin", likely with pores <4.4 nm, has also been suggested as a defense against viral attack of the cells within the colony (Hamm et al 1999). To test these hypotheses is nevertheless not easy as colonies will always shed at least some single cells, which become readily infected.…”
Section: Resistance To Viral Infectionmentioning
confidence: 99%
“…The mucopolysaccharides consist of at least nine different aldoses, are watersoluble, and polymers are larger than 1,000 kDa (Janse et al 1999). Qualitative staining of the colony matrix indicated the absence of lipophilic compounds and chitin, but the presence of amino groups (Hamm et al 1999). Matrix-assisted laser desorption/ionization (MALDI) analysis showed that N was not proteineous, but probably present in aminosugars (Solomon et al 2003).…”
Section: Mucopolysaccharidesmentioning
confidence: 99%
“…The negatively charged mucopolysaccharides become entangled and form ionic links, such as calcium bridges (Van Boekel 1992). They then form a thin, yet strong, semipermeable colony matrix, with a pore size between 1 and 4.4 nm diameter, with plastic and to a limited extent also elastic properties (Kornmann 1955;Hamm et al 1999). Electron microscope studies of a Phaeocystis sp.…”
Section: Mucopolysaccharidesmentioning
confidence: 99%
“…The colonial stage, with cells very loosely interconnected and enclosed in a thin skin (Hamm et al 1999), is most easily recognized, although some species may form mucilaginous colonies or do not seem to have a colonial stage. Thousands of cells can occur in a colony that may reach 2 cm in diameter (Jahnke and Baumann 1987;Verity et al 1988;Rousseau et al 1994;Davidson and Marchant 1992).…”
Section: Introductionmentioning
confidence: 99%